2010
DOI: 10.1007/s11033-010-0270-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in microRNA genes and prostate cancer risk in North Indian population

Abstract: Recent evidence indicates the involvement of microRNAs (miRNAs), in cell growth control, differentiation, and apoptosis, thus playing a role in tumorigenesis. Single-nucleotide polymorphisms (SNPs) located at miRNA-binding sites (miRNA-binding SNPs) are likely to affect the expression of the miRNA target and may contribute to the susceptibility of humans to common diseases. We genotyped SNPs hsa-mir196a2 (rs11614913), hsa-mir146a (rs2910164), and hsa-mir499 (rs3746444) in a case-control study including 159 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 28 publications
7
88
0
2
Order By: Relevance
“…As shown in Figure 2, the G-allele of rs2910164 had a higher representation in cases and controls of Caucasian populations (75.07 and 76.58%, respectively) than in those of Asian populations (50.42 and 47.88%, respectively). The distribution of all the genotypes in the controls was consistent with the HWE in all studies, except for 3 studies (Catucci et al, 2010;George et al, 2011;Mittal et al, 2011). Several studies collected information on possible confounding factors, such as smoking status (Guo et al, 2010;Xu et al, 2010;Zeng et al, 2010) and gender (Xu et al, 2008;Zeng et al, 2010;Akkiz et al, 2011), and the gene-environment interaction effect was ana-, and the gene-environment interaction effect was anaand the gene-environment interaction effect was analyzed in subgroups.…”
Section: Selection Of Studiesmentioning
confidence: 66%
See 1 more Smart Citation
“…As shown in Figure 2, the G-allele of rs2910164 had a higher representation in cases and controls of Caucasian populations (75.07 and 76.58%, respectively) than in those of Asian populations (50.42 and 47.88%, respectively). The distribution of all the genotypes in the controls was consistent with the HWE in all studies, except for 3 studies (Catucci et al, 2010;George et al, 2011;Mittal et al, 2011). Several studies collected information on possible confounding factors, such as smoking status (Guo et al, 2010;Xu et al, 2010;Zeng et al, 2010) and gender (Xu et al, 2008;Zeng et al, 2010;Akkiz et al, 2011), and the gene-environment interaction effect was ana-, and the gene-environment interaction effect was anaand the gene-environment interaction effect was analyzed in subgroups.…”
Section: Selection Of Studiesmentioning
confidence: 66%
“…The study selection process is shown in Figure 1. Finally, 22 articles (Jazdzewski et al, 2008;Xu et al, 2008;Hoffman et al, 2009;Hu et al, 2009;Tian et al, 2009;Catucci et al, 2010;Guo et al, 2010;Liu et al, 2010;Okubo et al, 2010;Pastrello et al, 2010;Srivastava et al, 2010;Xu et al, 2010;Zeng et al, 2010;Garcia et al, 2011;George et al, 2011;Akkiz et al, 2011;Hishida et al, 2011;Mittal et al, 2011;Permuth-Wey et al, 2011;Yue et al, 2011;Zhou et al, 2011;Zhou et al, 2012) with 11,901 cases and 14,200 controls were included in the present meta-analysis. An article by Catucci et al (2010) reported a case-control study of a German population and an Italian population separately, and one by Jazdzewski et al (2008) reported studies on populations of Finland, Poland, and USA separately.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…One study was excluded as it was not associated with hsa-mir-499 rs3746444 A>G (Kupcinskas et al, 2012). After further excluding two abstracts (Hu et al, 2009;Hwang et al, 2010), thirty-nine case-control studies involving 14,136 cases and 16,937 controls were selected for meta-analysis (Hu et al, 2009;Tian et al, 2009;Catucci et al, 2010;Liu et al, 2010;Okubo et al, 2010;Srivastava et al, 2010;Akkiz et al, 2011;George et al, 2011;Ling et al, 2011;Mittal et al, 2011;Vinci et al, 2011;Zhou et al, 2011;Alshatwi et al, 2012;Chu et al, 2012;Kim et al, 2012;Min et al, 2012;Xiang et al, 2012;Zhou et al, 2012;Ahn et al, 2013;Lv et al, 2013;Shan et al, 2013;Song et al, 2013;Umar et al, 2013;Vinci et al, 2013;Wei et al, 2013;Wu et al, 2013;Zou and Zhao, 2013;Bansal et al, 2014;Chu et al, 2014;Du et al, 2014;Gutierrez-Camino et al, 2014;Hasani et al, 2014;Hou et al, 2014;Hu et al, 2014;Ma et al, 2014;Omrani et al, 2014;Pu et ...…”
Section: Methodsmentioning
confidence: 99%
“…During the reading of the 25 full-text manuscripts, 4 studies were excluded due to incomplete rs11614913 polymorphism distribution data required for OR calculation (10)(11)(12)(13). For the remaining 21 records, baseline characteristics of the patients and control subjects were summarized, the study quality was assessed, HWE in particular was assessed by Chi-square test; two records involving Indian populations published in 2011 were excluded for disagreement with HWE (P<0.05) (14,15), thus leaving 19 articles identified with criteria for inclusion and exclusion (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). All studies were case-control studies.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%